Atmospheric Lamb wave pulse and volcanic explosivity index following the 2022 Hunga Tonga (South Pacific) eruption - Dalal, Prohelika; Kundu, Bhaskar; Panda, Jagabandhu; Jin, Shuanggen (Frontiers in Earth Science, 2023)
The atmospheric Lamb wave induced by the Hunga Tonga (South Pacific) volcanic eruption on 15 January 2022 was recorded as atmospheric pressure fluctuations at various meteorological stations around the globe, and persisted for several days after the eruption. This Lamb wave had not been reported from any eruption in the last two decades. In the present study, the barometric pressure change induced by the Lamb wave is used as a direct proxy to quantify the volcanic explosivity index (VEI) of this eruption. An empirical equation, which is used as a function of the size of the eruption and the distance of the barometric station from the source of eruption, determined from pressure-change data that the volume of the eruption was ∼8.6 km3. Accordingly, the VEI of the eruption is found to be 5. The VEI derived from the barometric pressure change is consistent with the VEI estimated through seismic waveforms, and hence can be considered a first-order parameter of the eruption.